ANOPHELES PSEUDOPUNCTIPENNIS THEOBALD A VECTOR OF MALARIA IN MEXICO - VARGAS, LUIS; EARLE WALTER, C; CASIS SACRE, GUILLERMO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1949)
The oil consists of the glycerides of linoleic acid (43%), oleic acid (601%), palmitic acid (300%), stearic acid (36%) The unsaponifiable matter amts to 2%
AM J TROP MED
Keywords: VECTOR, MALARIA, MEXICO; CIENCIAS MEDICAS; PATOLOGIA; PARASITOLOGIA